Epidermolysis bullosa pruriginosa - Puri Suruchi; Nanda Soni; Grover Chander; Reddy B (Wolters Kluwer Medknow Publications, 2005)
Epidermolysis bullosa (EB) pruriginosa is a rare distinct variant of dystrophic EB. It is characterized by extremely pruritic, lichenified or nodular lesions predominantly over legs, milia formation and albopapuloid lesions on the trunk. Toe nail dystrophy is a consistent finding in adult patients. The rarity of intact blisters, prominent nature of some of the scars and the marked lichenification with severe pruritus lead to a confusion with commoner disorders, like lichen simplex chronicus, lichen planus hypertrophicus and dermatitis artefacta. We present a rare and interesting case of EB pruriginosa where the diagnosis was confirmed with help of characteristic histopathology.